A mathematical model of HCV transmission dynamics with sex stratification and environmental effects - Mlyashimbi Helikumi; Josiah Mushanyu; Adquate Mhlanga (PLoS ONE, 2025)
This study primarily aims to determine how sex-specific behaviors influence Hepatitis C Virus (HCV) transmission dynamics among people who inject drugs (PWID), and to identify key parameters and interventions that most effectively reduce infection prevalence. Despite the availability of effective treatment, HCV remains a major public health challenge particularly among PWID, with sex-specific differences influencing the transmission dynamics. In this study, we developed a sex-structured deterministic mathematical model to investigate HCV transmission through contaminated needles, focusing on gender-specific patterns among PWID. Unlike previous models, our work separates transmission by sex and also captures differences between high-risk and low-risk injecting behavior through transmission and needle reuse parameters.The model classifies the population into distinct HCV related compartments for both males and females, while also incorporating an environmental pool of contaminated needles. We computed and analyzed the systems reproduction threshold and steady states, identifying conditions under which the disease persists and scenarios where backward bifurcation may occur. Sensitivity analysis identified the most influential factors on acute infection prevalence, such as rates of needle contamination, sex-specific contact behaviors, and recovery outcomes among males. Simulation results show that males experience a higher burden of acute and chronic HCV infections. Increasing the viral decay rate in needles leads to a notable decline in infections, highlighting the effectiveness of environmental interventions like needle sterilization. Additionally, reducing risky behaviors in both sexes produces the largest overall reduction in transmission, while improving needle exchange efforts by lowering the reuse of uncontaminated needles further suppresses disease spread. Our findings highlight the need for integrated harm reduction with enough, gender informed coverage, particularly ensuring sufficient reach among men, while future work should evaluate sex differential uptake and efficacy.